The genome sequence of the Heath Bumblebee, Bombus jonellus (Kirby, 1802) [version 1; peer review: 2 approved] - Gavin R. Broad; Chris Fletcher; Inez Januszczak (Wellcome Open Research)
We present a genome assembly from a female specimen of Bombus jonellus (Heath Bumblebee; Arthropoda; Insecta; Hymenoptera; Apidae). The genome sequence has a total length of 357.90 megabases. Most of the assembly (78.06%) is scaffolded into 18 chromosomal pseudomolecules. The mitochondrial genome has also been assembled, with a length of 24.83 kilobases.